Profile of biologically active substances of Aronia mitschurinii leaves growing in the conditions of the Central Black Earth region - O. V. Trineeva; O. V. Pugacheva (Разработка и регистрация лекарственных средств, 2024)
Introduction. Aronia Мitschurinii (Aronia × mitschurinii A.K. Skvortsov & Maitul) is a species obtained by crossing chokeberry (Aronia melanocarpa (Michx.) Elliott) and mountain ash (Sorbus aucuparia L.). This plant is more widely known in the literature as chokeberry. Mitschurin сhokeberry is actively cultivated in the Russian Federation (RF) and neighboring countries to obtain the main raw material – fruits. Aronia should not be confused with chokeberry, which does not grow wild and is practically not cultivated in the Russian Federation due to the inedibility of the fruit and the low decorative value of the plant. The leaves, unlike the fruits, of Mitschurin chokeberry are not yet used as medicinal plant raw materials (MPR). However, according to preliminary studies, they are a promising source of biologically active substances (tannins, flavonoids, leukoanthocyanins, vitamins, a complex of microelements, etc.), exhibiting astringent, antioxidant and anti-inflammatory activities. Therefore, an urgent task is to develop indicators of the authenticity of raw materials based on the presence of the main groups of biologically active substances, as well as methods and standards for their quantitative content for the formation of draft regulatory documentation for Michurin chokeberry leaves.Aim. The purpose of the study was to study the profile of biologically active substances of Michurin chokeberry leaves, growing in the territory of the Central Black Earth Region of the Russian Federation, to determine the target groups that determine the pharmacological activity of this raw material.Materials and methods. Leaves of Michurin chokeberry for research were harvested during the period of technical maturity of the fruit (August – September 2023) from a plant cultivated in the city of Michurinsk (Tambov region) and dried. Primary screening was carried out for the presence of individual groups of biologically active substances in the leaves of Michurin chokeberry, using known qualitative reactions. The composition of flavonoids was determined by thin layer chromatography. Quantitative determination of the main groups of biologically active substances was carried out according to known methods using modern physicochemical methods of spectrophotometry and capillary electrophoresis.Results and discussion. Tannins, flavonoids, alcohol-soluble saponins, leukoanthocyanins, amino acids, ascorbic acid and polysaccharides in the form of mucilage were found in the leaves of Aronia mitschurinii. No alkaloids were found. TLC analysis of flavonoids revealed at least 4 adsorption zones with yellow-green fluorescence, one of which was identified as rutin. The thiamine content in the leaves was 0.99 ± 0.084 mg/kg; riboflavin – 0.43 ± 0.025 mg/kg; choline – 44.4 ± 3.9 mg/kg; extractives – 31.52 ± 0.22 %; the amount of flavonoids in terms of rutin – 3.48 ± 0.21 %; the amount of tannins in terms of catechin – 8.63 ± 0.32 %; the amount of anthocyanins in terms of cyanidin-3-O-glucoside – 11.62 ± 0.69 %. In the leaves of Aronia mitschurinii, 17 amino acids were identified (total content 5.88 %), 7 of them are essential (2.71 %). The predominant amino acids are leucine and glutamic acid – 18.37 and 10.88 % of the total amino acid content, respectively. The quantitative content of eight free organic acids was also determined (total content 0.49 %). The predominant acids are citric, malic and sorbic.Conclusion. As the target groups of biologically active substances responsible for the pharmacological activity of Aronia mitschurinii leaves, it is most rational to consider a complex of polyphenols (flavonoids, anthocyanin compounds and tannins), the content of which is quite high. According to the spectral characteristics, the dominant biologically active substances in the sum of flavonoids, tannins and anthocyanins are rutin, catechin and cyanidin-3-O-glucoside, respectively. This type of raw material can be considered as a promising source of biologically active substances for the purpose of further obtaining herbal plants preparations with antioxidant, capillary-protective, astringent and anti-inflammatory effects.